Extensive porto-splenic venous thrombosis postsplenectomy in a sickle cell disease: a rare complication. Issue 1 (17th January 2022) - Al Barhi, Tamadher; Wali, Yasser; Al Sibai, Sareyah; Al Balushi, Zainab
Abstract : Hereditary haemoglobinopathies are common disorders in Oman. The most common haematological disorder among Omani population is sickle cell disease (SCD). The spleen is one of the organs that is affected early in the first decade of life in SCD patients. Splenectomy has shown a high success rate in improving the quality of life in SCD patients, through eliminating acute splenic sequestration crises, thus reducing the need for hospital admission and transfusion requirements. One of the rare complications of splenectomy is porto-splenic vein thrombosis. Multiple factors are responsible for this complication including: thermal and mechanical injury during ligation of splenic hilum, sudden increase in the platelet count and large spleen size. We report a rare case of extensive porto-splenic vein thrombosis that responded to early initiation of anticoagulation with resolution of the thrombosis and recanalisation.